Education as a Factor in the Quality of Adult Leisure Time - Andrić, Aleksandra M.; Dobrić, Tamara M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Leisure is an integral part of every man's life and, therefore, has rich manifestations in the field of education. The way it is organized and used has a great influence on the formation of versatile personality. Namely, the adequate organization of leisure time can positively affect health and physical and mental development. Since free time is a category that follows the development of society, it can be said that changes in the development of the society influence both the spheres of human life and leisure time. The notion and basic characteristics of free time have been the subject of numerous debates and researches by many pedagogues, sociologists, psychologists, philosophers, etc. A number of authors agree that the potential of developing personality can be analysed and explained within the context of free time. The aim of the paper is to demonstrate whether education can affect the quality of adult leisure time. In this regard, the work emphasizes the presence, importance, as well as the action of certain factors that can influence the process of organization and realization of leisure time.
Keywords: adult education; education; leisure; leisure time